Effects of kettlebell swing vs. explosive deadlift training on strength and power - Maulit, M. R.; Archer, D. C.; Leyva, W. D.; Munger, C. N.; Wong, M. A.; Brown, L. E.; Coburn, J. W.; Galpin, A. J. (International Journal of Kinesiology & Sports Science, 2017)
Recent research has compared explosive deadlift to kettlebell training observing their effects on strength. The kettlebell swing is a popular practical exercise as it shares share a hip hinge movement with the explosive deadlift, but the two have not been compared. Objectives: The purpose of this study was to compare the effects of kettlebell swing vs. explosive deadlift training on strength and power. Methods: Thirty-one recreationally resistance-trained men (age = 23.1 ± 2.3 years, height = 175.5 ± 6.6 cm, mass = 83.9 ± 13.8 kg, 1RM deadlift = 159.9 ± 31.7 kg) were randomly assigned to one of two groups [kettlebell swing group (KBG) n = 15, or explosive deadlift group (EDLG) n = 16]. Vertical jump height, isometric mid-thigh pull (MTP), and 1RM deadlift were measured pre and post training. Both groups trained twice per week for 4 weeks. Volume and load were increased after the first 2 weeks of training. Results: A 2 (time) x 2 (group) mixed factor ANOVA revealed a significant (P<0.05) increase in deadlift 1RM (pre: 159.9 ± 31.7 kg, post: 168.9 ± 31.8 kg) and vertical jump height (pre: 56.6 ± 9.9 cm, post: 57.9 ± 9.7 cm) for both groups, but were not significantly different between groups. There were no significant changes in MTP. Conclusions: Strength and conditioning professionals may use both kettlebell swings and explosive deadlifts to increase deadlift strength and vertical jump power.